45S5 BAG-Ti6Al4V structures: The influence of the design on some of the physical and chemical interactions that drive cellular response - Melo-Fonseca, F. (2018)
Multi-material Ti6Al4V cellular structures impregnated with 45S5 bioactive glass were designed and produced using Selective LaserMelting (SLM), an additive manufacturing technique, combinedwith Press and Sintering focusing on load bearing components like hip implants. These structures were designed to combine Ti6Al4V mechanical properties and promote bone ingrowth into the structure as the bioactive material (45S5) is being absorbed and replaced by newly formed bone. The influence of these structures design on some of the physical and chemical aspects that drive cellular response was assessed. Roughness, wettability, bioactive glass quantity and quality on the structures after processing and the pH measured during cell culture (as a consequence of bioactive glass dissolution) were evaluated and correlated with cellular viability, cellular distribution, morphology and proliferation on the surface and inside the structures.